Children of Karl and Fritz Kautsky. Probably from left to right: Fritzi, Felix, Else and Benedikt. With dedication from Anna Dietzgen: "Zur freundlichen Erinnerung an St. Gilgen 1902"
Children of Karl and Fritz Kautsky. Probably from left to right: Fritzi, Felix, Else and Benedikt. With dedication from Anna Dietzgen: "Zur freundlichen Erinnerung an St. Gilgen 1902".